Improvement of thermohydraulic performance of flow based on novel dimpled tubes on response surface methodology and Taguchi technique-fitted experiment design - Ahmed Ramadhan Al-Obaidi; Anas Alwatban (International Journal of Thermofluids)
Analysis of thermal flow and the heat performance with dimple pipes under various geometric configurations are carried out in the current study. The focus of the current research work is on behavior of thermal flow characteristics, pressure, and different velocity components in heat exchanger pipes that have inner pipe wall dimples. The study employs the CFD technique to perform three-dimensional computational computations to investigate the impact of four geometrical parameters on thermo-hydraulic performance enhancement: dimple pitch, dimple diameter, dimple number, and dimple distance between dimples. Additionally, the Taguchi and Response Surface Methods in conjunction with design of experiments (DOE) methodologies are used to optimize the impact of the following factors. The utilization of dimples on inner surface of wall tube caused distinct patterns in the flow and heat performance, according to the results. Additionally, by using dimples, the area of heat performance can be increased because of the interactions that occur between the swirling flow and the dimpled wall surfaces, which enhance heat transfer performance. A thorough flow investigation between the dimples and wall pipe describes the reasons for the changes in heat transmission and pressure. Compared to smooth pipe, optimal design of dimpled pipe was improved approximately 35.8% and 36.2%, according to results of an orthogonal experiment conducted in this investigation using the computational fluid dynamic method with DOE, RSM, and TM for temperature differences and rate of heat. The results indicate that there was a high value of higher than one for the performance evaluation factor (PEF). The aforementioned findings suggest that dimple optimization, enhanced heat transfer efficiency, and the flow of hydrodynamic analysis are necessary for a variety of design applications. Difference between the present numerical and experimental data for Nu and f factours which were around 7.5 and 6.5%.